Regulation by Nitric Oxide of Endotoxin-Induced Tissue Factor and Plasminogen Activator Inhibitor-1 in Endothelial Cells - Pérez-Ruiz, Ana; Montes, Ramón; Velasco, Francisco; López-Pedrera, Chary; Páramo, José Antonio; Orbe, Josune; Hermida, José; Rocha, Eduardo (Thrombosis and Haemostasis, 2002)
The increase in nitric oxide (NO) production in lipopolysaccharide (LPS)-induced sepsis is thought to contribute to the development of shock. However, NO could also play an antithrombotic role. Little is known about the modulating effect of NO on the endothelial overexpression and production of tissue factor (TF) and plasminogen activator inhibitor-1 (PAI-1) occurring in endotoxemia. We analyzed the effect of N(G)-nitro-L-arginine-methyl-ester (L-NAME), an inhibitor of NO synthases, and S-nitroso-N-acetyl-D,L-penicillamine (SNAP), a NO donor, on the expression and synthesis of TF and PAI-1 by LPS-challenged human umbilical vein endothelial cells (HUVEC): L-NAME enhanced the increase in TF mRNA and antigen levels (P <0.05) observed in LPS-treated HUVEC; SNAP down-regulated the LPSinduced TF increment (p <0.05). However, no effects of NO on regulation of the LPS-dependent increase in PAI-1 could be seen. Thus, NO could play an antithrombotic role in sepsis by down-regulating the endothelial overexpression and production of TF.
Keywords: HUVEC; Sepsis; Nitric oxide; Tissue factor; Plasminogen activator inhibitor-1